1996
DOI: 10.1111/j.1600-051x.1996.tb02075.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the healing response following placement of Coe‐pak and an experimental pack after periodontal flap surgery

Abstract: 2 periodontal dressings, Coe-pak and RD8 (a product under development), were assessed following periodontal surgery, using a double-blind study of randomised split-mouth design, with each patient acting as their own control. Matched sites were selected for periodontal flap surgery under local analgesia. Sites were randomly allocated to each group. The dressings were applied by a single operator and both patients and clinical assessors were blind as to the dressing employed. The dressings were assessed as to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 30 publications
1
15
0
5
Order By: Relevance
“…),[8] and bleeding index (Muhlemann et al .). [5] Pain and discomfort were recorded using the visual analogue scale (VAS). [5] All the evaluations were made by the same examiner (VB) who was blinded for the surgical procedures and pack applications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…),[8] and bleeding index (Muhlemann et al .). [5] Pain and discomfort were recorded using the visual analogue scale (VAS). [5] All the evaluations were made by the same examiner (VB) who was blinded for the surgical procedures and pack applications.…”
Section: Methodsmentioning
confidence: 99%
“…Although widely accepted, Coe-pak has a number of disadvantages, e.g., poor appearance, ill-defined setting time, and poor flow properties during manipulation. [5]…”
Section: Introductionmentioning
confidence: 99%
“…Stahl et al (1969) demonstrated that the placement of standard periodontal dressing and oral adhesive bandage after gingivectomy had little influence on the healing process. In addition, several other studies with periodontal dressings applied after flap operation have confirmed such conclusions (Jones and Cassingham, 1979;Allen and Caffesse, 1983;Cheshire et al, 1996). Furthermore, the possibility that bacterial plaque may be found between the dressing and the tissue surface also questions the effectiveness of periodontal packs.…”
mentioning
confidence: 89%
“…Coe-pak as periodontal dressing has been used since long, however its justified and reasoning for application is still questionable. Recently application of light cure dressing material Barricaid offers more superior and acceptable results as compared to standard periodontal dressings especially for anterior region 3,11 . According to manufacture guidelines this material is aesthetically pleasing, ease to handle and manipulate and under operator"s control for rate of curing.…”
Section: Discussionmentioning
confidence: 99%
“…These periodontal dressings were found to cause allergic reaction, hence non -eugenol periodontal dressings mainly "Coe -pak" (GC America, Inc. USA) offers a standard and widely used after periodontal surgery. 3 Coe -pak has been successfully used after locally delivered drug, 4 gingivectomy, 5 apically repositioned flap 6 , periodontal regenerative surgery 7 , mucogingival surgery 8 . Even after long term use, Coe -pak has some drawbacks related to handling, manipulation, appearance and adhesive properties.…”
Section: Introductionmentioning
confidence: 99%